Use-Trace Epistemology and the Logic of Inference. (1st October 2016) - Bradfield, Justin
Abstract : Use-trace analyses are regularly used to provide clues about artifact functionality and the use of materials that do not preserve and which are therefore not represented in the archaeological record. While all sciences strive for deductive certainty, they generally make use of inductive and abductive arguments. The same is true of use-trace studies. Here I examine the three main types of logical inference used in archaeological science and the extent to which each one is used in the interpretation of ancient use-traces. Each type of inference provides a different degree of certainty, and it is suggested that use-trace analysts should acknowledge this when presenting the interpretation of their results. Use-traces develop on tools through mechanical processes. They are then used to infer the most appropriate and likely anthropic activity to account for their formation. Despite the appeal to mechanical laws or regularities, the process of imputing anthropogenic activity to these use-traces is abductive and as such carries with it the same logical surety as all abductive inferences.